Effects of deep brain stimulation target on the activation and suppression of action impulses. (December 2022) - Dietz, Nicholas; Alhourani, Ahmad; Wylie, Scott A.; McDonnell, Jessica L.; Phibbs, Fenna T.; Dawant, Benoit M.; Rodriguez, William J.; Bradley, Elise B.; Neimat, Joseph S.; van Wouwe, Nelleke C.
Highlights: We studied effects of deep brain stimulation in subthalamic nucleus and globus pallidus on action control processes. Stimulation in both targets induces fast impulsive action errors. Stimulation in the subthalamic nucleus and globus pallidus also improves selective inhibitory control. Abstract: Objective: Deep brain stimulation (DBS) is an effective treatment to improve motor symptoms in Parkinson's disease (PD). The Globus Pallidus (GPi) and the Subthalamic Nucleus (STN) are the most targeted brain regions for stimulation and produce similar improvements in PD motor symptoms. However, our understanding of stimulation effects across targets on inhibitory action control processes is limited. We compared the effects of STN (n = 20) and GPi (n = 13) DBS on inhibitory control in PD patients. Methods: We recruited PD patients undergoing DBS at the Vanderbilt Movement Disorders Clinic and measured their performance on an inhibitory action control task (Simon task) before surgery (optimally treated medication state) and after surgery in their optimally treated state (medication plus their DBS device turned on). Results: DBS to both STN and GPi targets induced an increase in fast impulsive errors while simultaneously producing more proficient reactive suppression of interference from action impulses. Conclusions: Stimulation in GPi produced similar effects as STN DBS, indicating that stimulation to either target increases the initial susceptibility to act on strong action impulses while concomitantly improving the ability to suppress ongoing interference from activated impulses. Significance: Action impulse control processes are similarly impacted by stimulating dissociable nodes in frontal-basal ganglia circuitry.